The use of procalcitonin in patients with surgical forms of erysipelas - S.D. Shapoval; L.A. Vasylevska (Medičnì Perspektivi, 2021)
The ideal marker of bacterial infection should not only allow for early diagnosis, but also provide information about the course and prognosis of the disease. Nowadays the most well-studied and widely used in clinical practice is procalcitonin (PCT), but its value in surgical forms of erysipelas is insufficiently defined. The aim of the article is to determine the diagnostic and prognostic significance of procalcitonin in patients with surgical forms of erysipelas.114 case histories of patients who were hospitalized in the center of purulent-septic surgery of the Non-profit municipal enterprise "City Hospital №3" in Zaporozhye for 2019-2020 period were analyzed retrospectively and prospectively. It was found that most often the focus was localized on the lower extremities. In the complex treatment of patients with erysipelas, the main place belongs to antibiotic therapy (ABT) and early surgical treatment of the area of the pathological process. Determination of the level of procalcitonin in the serum makes it possible to assess the progression and generalization of the process and is a sensitive test for the effectiveness of treatment.Radical surgery and timely targeted ABT are key elements of success in the treatment of surgical forms of erysipelas and are not subject to revision. Procalcitonin is a diagnostic marker that can predict the development of sepsis.